2015
DOI: 10.1186/s13638-015-0401-7
|View full text |Cite
|
Sign up to set email alerts
|

Robust indoor localization and tracking using GSM fingerprints

Abstract: The article presents an easy to implement approach for indoor localization and navigation that combines Bayesian filtering with support vector machine classifiers to associate high-dimensionality cellular telephone network received signal strength fingerprints to distinct spatial regions. The technique employs a "space sampling" and a "time sampling" scheme in the training procedure, and the Bayesian filter allows introducing a priori information on room layout and target trajectories, resulting in robust room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…In [30], it is shown that SVM and LS-SVM are equivalent under mild conditions. From constraints (19) and the fact that t i = ±1 we have…”
Section: Support Vector Machinesmentioning
confidence: 99%
See 4 more Smart Citations
“…In [30], it is shown that SVM and LS-SVM are equivalent under mild conditions. From constraints (19) and the fact that t i = ±1 we have…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…The last equality comes from the strong law of large numbers. In the limit, the optimization problem (19) is equivalent to…”
Section: Support Vector Machinesmentioning
confidence: 99%
See 3 more Smart Citations